Kemampuan Berpikir Kritis Siswa melalui Studi Kasus Materi Antroposfer - Wa Ode Samlia; Sunarty Suly Eraku; Nurfaika Nurfaika (Universitas Negeri Gorontalo, 2026)
This descriptive qualitative study aims to describe the critical thinking skills of grade X students in learning Anthroposphere material through case-based deep learning at SMAN 2 Konawe Selatan. The study involved 24 students and one geography teacher. Data were collected through classroom observation, case-based essay tests, interviews, and documentation, then analyzed descriptively using triangulation of techniques and sources. The results show that the learning process reflected meaningful, mindful, and joyful learning. Students achieved an average score of 92.71, with all students categorized as very critical. The findings indicate that contextual cases can support students in interpreting geographic phenomena, analyzing causal relationships, drawing evidence-based conclusions, evaluating alternative solutions, and presenting reflective explanations of population and environmental issues.